تقدير شدة الصقيع وتواتره في مناطق مناخية مختلفة من سورية - جـلب, أدهـم; شيخو, طاهر (Latakia University Journal -Biological Sciences Series, 2019)
الصقيع هو أحد المخاطر الطبيعية التي تهدد الإنتاج الزراعي وتلحق أضراراً جسيمة بالمحاصيل الزراعية وأشجار الفاكهة المتأثرة به وذلك تبعاً لأطوار نموها. تتأثر المناطق الداخلية والجبلية من القطر العربي السوري بشكل خاص بالصقيع، إذ يمكن أن يقضي على مجمل إنتاج الخضراوات أو الفاكهة في بعض السنوات. أظهرت نتائج هذا البحث تقدير شدة الصقيع وتواتره خلال الفترة الممتدة من 1975 حتى 2006 في أربع مناطق مناخية مختلفة من القطر (الحسكة، والرقة، وحماه وإدلب).حيث أظهرت النتائج تردد الصقيع الخفيف بشكل أكبر من باقي المستويات وغياب كامل للصقيع الشديد جداً في جميع مناطق الدراسة. وتميزت الحسكة بأكبر عدد من حالات الصقيع بأنواعه ومستوياته المختلفة وعلى كامل المقاييس الزمنية تلتها الرقة ومن ثم حماه وأخيراً إدلب. Frost is one of the natural hazards, that threaten agricultural production, and causes significant damages to the affected crops and fruit trees depending on their phonological stages. Syrian inland and highlands areas are particularly affected by frost that may destroy the whole production of vegetables or fruits in certain years. This research estimated frost severity and frequency for the period extended from 1975 to 2006 in four different climatic regions of the country (Hassakeh, Raqqa, Hama and Idleb). Results showed that slight frost was the most frequent in all studied areas comparing with the other levels of the degrees of frost severity, and the absence of very severe frost. The greatest number of frost cases with its various types and levels and on all the temporal scales characterized Hassakeh region followed by Raqqa, Hama and finally Idleb.